Mobility-Aware Bivariate Line-of-Sight Probability for Air-to-Ground Communications Using Millimeter and Terahertz Waves - Basheer Ameen Raddwan; Ibrahim Ahmed Al-Baltah (IEEE Access)
This paper presents a mobility-aware bivariate line-of-sight (LoS) probability model for millimeter waves and terahertz air-to-ground communication. Current literature does not provide LoS models that consider using directional antennas on the unmanned aerial vehicle that acts as an air base station (airBS). Furthermore, in the context of having large stationary blockers, the impact of ground user terminals’ (gUTs) and airBSs’ mobility remains unexplored. To simulate the ray-tracing between gUTs and airBSs in both scenarios where the airBSs have omnidirectional or directional antennas, we develop a game engine-based synthetic urban layout generator. We analyze ray-tracing as a bivariate probability and formulated a unified joint probability function that could predict the LoS probability for omnidirectional and directional scenarios. The proposed model outperformed the existing models in the omnidirectional scenario. We also present a benchmark for the model’s performance in the directional scenario. Moreover, using ray-tracing simulation, we examine the influence of mobility on the service time, also known as the sojourn time, and developed two cubic polynomial models to forecast the service time for any urban layout that aligns with the ITU-R P.1410-5 build-up parameters.